Enhanced Performance of the 4 × 20 Gbit/s-40 GHz OFDM-Based RoFSO Transmission Link Incorporating WDM-MDM of Hermite Gaussian and Laguerre Gaussian Modes - Singh, Karamjeet; Singh, Mehtab; Grover, Amit; Miglani, Rajan; Singh, Harjeevan; Amhoud, El Mehdi (Frontiers in Physics, 2022)
A 4 × 20 Gbit/s-40 GHz orthogonal frequency-division multiplexing-based radio-on-free-space optics information link, integrating hybrid wavelength- and mode-division multiplexed transmission techniques, is proposed in this paper. Furthermore, an ameliorated detection scheme deploying a square root module after each photo diode at the receiver terminal is proposed to mitigate the adverse performance effects because of nonlinear photodiode characteristics. The presented results show a successful 80 Gbit/s-160 GHz transmission at 3000 and 2700 m under heavy rainy and foggy weather, respectively. The link demonstrates superior performance in terms of maximum range and transmission rate compared to previous works.